PENGARUH FRONT TIME TERHADAP KARAKTERISTIK PERLINDUNGAN ARESTER ZnO DAN SiC 18 KV - , RIKY DWI PURIYANTO, Prof. Dr. Ir. T. Haryono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Silicon carbide (SiC) and metal oxide (ZnO) arrester are protection equipment of high voltage system against overvoltage due to lightning. Lightning produces more electric charge in some electric power line. Lightning surge which flow through long electric power line can modify lightning waveform, one of which is the change in the value of front time. Therefore, it is important to know the effect of front time to the arresters residual voltage of two different kind of arresters. The research was conducted through laboratory-scale testing using major equipment such as high voltage generator, impulse voltage generator, and oscilloscope. Modified value of the inductor in impulse voltage generator circuit produce different value of the front time of lightning (< 45Î¼s). Then input voltage having different value of front time were applied to both arresters. We must vary input voltage to get comparable amplitude of impulse voltage (60 kV and 100 kV). According to the test, it is known that variation of front time gave effect to both arrester, SiC and ZnO. In SiC arrester, the higher value of the front time resulted in a decrease in the value of residual voltage. The average value of residual voltage was 33.51 kV for 60 kV input voltage and 39.91 kV for 100 kV input voltage. In ZnO arrester, the higher value of front time resulted in a decrease in the value of residual voltage until reaching the peak time of 17 microseconds. The average value of ZnO arrester residual voltage was 39.97 kV for 60 kV input voltage and the 42.15 kV for 100 kV input voltage. The entire test result indicated SiC arrester residual voltage value lower than ZnO arrester.